Subclinical Hypothyroidism in Patients with Diabetic Retinopathy: Role of Vascular Endothelial Growth Factor - El-Sehrawy, Amr A.; Elkhamisy, Enas M.; Badawi, Amani E.; Elshahawy, Heba A.; Elsayed, Eman; Mohammed, Nehal T.; El-Eshmawy, Mervat M. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: This study was conducted by considering the vital role of Vascular Endothelial Growth Factor (VEGF) in the development of Diabetic Retinopathy (DR) on the one hand and the frequent association between Subclinical Hypothyroidism (SCH) and DR on the other hand. Objective: The present study was proposed to explore the possible role of VEGF in the relation between SCH and DR; thus, we investigated the relationship between SCH and VEGF levels in patients with DR. Methods: Two hundred patients with DR were recruited in this study [100 patients with Proliferative Diabetic Retinopathy (PDR) and 100 patients with Non-Proliferative Diabetic Retinopathy (NPDR)]. Patients with DR were divided into 2 groups according to thyroid function, patients with SCH or those with euthyroidism. Patients were subjected to careful history taking and underwent clinical and ophthalmological examination. Fasting blood glucose, glycosylated hemoglobin, fasting insulin, Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), TSH, FT4, FT3, VEGF, and thyroid volume were assessed. Results: Among all the studied patients, 21.5% (43/200) had SCH. DR patients with SCH had older age, longer diabetes duration, and higher HbA1c, HOMA-IR, and VEGF than those with euthyroidism. The frequency of PDR in patients with SCH was 72.1% (31/43) and 43.9% (69/157) in those with euthyroidism, whereas the frequency of NPDR in patients with SCH was 27.9 (12/43) and 56.1% (88/157) in those with euthyroidism (P 0.003). In multivariate analysis, PDR, HOMA- IR, and VEGF levels were the significant predictor variables of SCH. Conclusion: Increased VEGF levels may be implicated in the relationship between SCH and DR.
Keywords: glycemic control